Biocarbonation of reactive magnesia for soil improvement - Yang, Yang (2022)
This paper presents a new microbial technique for soil improvement through microbially induced carbonate precipitation (MICP) incorporating with reactive magnesia cement (RMC). Through a microbially induced carbonate precipitation (MICP) process, hydrated magnesium carbonates (HMCs) are produced due to biological carbonation of hydrated RMC, which then act as cementation agents to bind soil particles. The influence of several parameters including the RMC content, urea content, and water content on the MICP efficiency was investigated. The performance of the biocarbonated RMC-based sand samples was evaluated using unconfined compressive strength and permeability measurements. Microstructural analyses including scanning electron microscope, X-ray diffraction, and thermogravimetric analysis were also performed to understand the mechanisms behind the treatment. Biocarbonated RMC-based sand samples were compared with the biocement-treated samples using the conventional MICP method. The experimental results indicated the formation of different types of biocarbonation phases enabled by the carbonate ions produced by urea hydrolysis via microbial metabolism. These phases, identified as HMCs, have provided strong bonding to loose sand particles to increase its early strength. The HMCs also occupy the pores of sand matrix to reduce its permeability. The unconfined compressive strength gained at 28 days was up to 2.3 MPa, and the reduction in permeability was up to 1.8 × 10−7 m/s among the tests carried out. The obtained findings have demonstrated that the biocarbonation of reactive magnesia approach is effective for soil improvement.